CITA HUKUM POSITIF INDONESIA DAN ASEAN ECONOMIC COMMUNITY (AEC) - Ahmad Hunaeni Zulkarnaen (Jurnal Hukum Mimbar Justitia, 2016)
ASEAN Economic Community, is a society that is integrated each other within the scope of ASEAN where free trade among the ASEAN members by the aim to create ASEAN become more stable, prosperous and competitive in development economically, with the following characteristics: (a) based on a single market and production, (b) highly competitive in regions economy, (c) equitable development in regions economy, and (d) integrated regions in the global economy.All of the Indonesian legal systems are created and applied for the implementation of the "ASEAN Economic Community (AEC) must be an intermediary and a gateway in achieving fairness and prosperity for Indonesian citizens based on Pancasila .Â Keywords : Â ASEAN Economic Community (AEC), fairness, prosperity.